Conditions for Exercising the Right to Resolution: Array - Niculescu, Liliana (Journal of Danubian Studies and Research, 2021)
With the entry into force of the Civil Code in 2009, Romanian private law has crossed the threshold of a substantial change in the termination of the contract. Traditionally, the resolution of the contract was seen as an extraordinary event, which could operate only in court, at the request of the creditor dissatisfied with the breach of contract by his debtor. Over time, the rigor of this rule was mitigated by the possibility for the parties to issue a conventional resolution admitting in doctrine and judicial practice, by inserting into the contract the so-called commissioners' pacts, which produced effects of different intensity depending on how were drafted. The new regulation adopts a major change in the legislator's perspective on the resolution, expressly recognizing at the principle level, in addition to the option of judicial resolution, the possibility to trigger the resolution and unilaterally, in the absence of a court decision or a contractual clause specific in this regard. The resolution is not just a sanction or one of the many legal remedies available to the creditor in response to the non-performance of the contract. It is not an end in itself (as opposed to the nullity of the contract), but it is a legal technique, a mechanism, which has many facets. In the Civil Code, the resolution of the contract is presented together with the termination considering the similarities between the two institutions, which we can consider decisive and defining points of support for understanding the evolution of contract theory and execution of obligations in Romanian private law. Although, in appearance, the new provisions on resolution do not substantially change, a systematic analysis of the provisions on the performance of contractual obligations leads to another conclusion. For this reason, we have chosen through this article to focus on identifying the characteristic features of this institution, insisting on the unique substantive condition necessary for the exercise of the right to terminate the contract.